2019
DOI: 10.1002/jso.25588
|View full text |Cite
|
Sign up to set email alerts
|

Giant cell tumors combined with secondary aneurysmal bone cysts are more likely to develop postoperative recurrence: A retrospective study of 256 cases

Abstract: Purpose The epidemiology and clinicopathology of aneurysmal bone cysts (ABCs) secondary to giant cell tumors of bone (GCTBs) have been well documented in the previous literature. However, reports on whether secondary ABCs could affect the postoperative recurrence of GCTBs are rare. This study analyzed the effects of secondary ABCs and other relevant clinical factors on the postoperative recurrence of GCTBs of the extremities. Methods We retrospectively analyzed 256 cases of GCTBs of the extremities that were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 25 publications
0
15
1
Order By: Relevance
“…The reason for the high recurrence rate of GCTB in the hand and foot is that the cortical window needs to be small as the bones in this location are smaller, making it difficult to perform aggressive curettage [59]. The presence of a fluid-fluid interface suggests a secondary aneurysmal bone cyst, while the presence of a secondary aneurysmal bone cyst increases the local recurrence rate after curettage [62,63]. Tang et al reported that secondary aneurysmal bone cysts were found in 60 (23%) of 256 patients with GCTB in the extremities; the local recurrence rate was 53% in the group with secondary aneurysmal bone cysts, while it was 26% in the group without secondary aneurysmal bone cysts (p < 0.05) [62].…”
Section: Giant Cell Tumor Of the Extremitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for the high recurrence rate of GCTB in the hand and foot is that the cortical window needs to be small as the bones in this location are smaller, making it difficult to perform aggressive curettage [59]. The presence of a fluid-fluid interface suggests a secondary aneurysmal bone cyst, while the presence of a secondary aneurysmal bone cyst increases the local recurrence rate after curettage [62,63]. Tang et al reported that secondary aneurysmal bone cysts were found in 60 (23%) of 256 patients with GCTB in the extremities; the local recurrence rate was 53% in the group with secondary aneurysmal bone cysts, while it was 26% in the group without secondary aneurysmal bone cysts (p < 0.05) [62].…”
Section: Giant Cell Tumor Of the Extremitiesmentioning
confidence: 99%
“…The presence of a fluid-fluid interface suggests a secondary aneurysmal bone cyst, while the presence of a secondary aneurysmal bone cyst increases the local recurrence rate after curettage [62,63]. Tang et al reported that secondary aneurysmal bone cysts were found in 60 (23%) of 256 patients with GCTB in the extremities; the local recurrence rate was 53% in the group with secondary aneurysmal bone cysts, while it was 26% in the group without secondary aneurysmal bone cysts (p < 0.05) [62]. The reason for the higher risk of local recurrence is that secondary aneurysmal bone cysts cause more bleeding and inadequate curettage [62].…”
Section: Giant Cell Tumor Of the Extremitiesmentioning
confidence: 99%
“…The existing literature on GCTB is mostly comprised of genetic and genomic studies and clinical case reports ( 68 , 69 ). These studies provide a basis for understanding the current treatment strategies for GCTB.…”
Section: Discussionmentioning
confidence: 99%
“…Although rigorous preoperative design, sophisticated surgical techniques, and standardized postoperative follow-up can maximize the benefit of patients, the risk of recurrence of RGCT remains [35,36]. The therapeutic regimen for recurrence post-operation can be referred to the initial recurrence, which is determined based on the specific conditions of the initial treatment, pathological characteristics, invasive extent, and tumor comorbidity after recurrence.…”
Section: Discussionmentioning
confidence: 99%